Air pollutant emission and reduction potentials from the sintering process of the iron and steel industry in China in 2017. (15th August 2022) - Liu, Jun; Wang, Si; Yi, Honghong; Tang, Xiaolong; Li, Zhangliang; Yu, Qingjun; Zhao, Shunzheng; Gao, Fengyu; Zhou, Yuansong; Wang, Yaxin
Abstract: The iron and steel industry (ISI) is one of the most energy-intensive industries in China, which makes a substantial contribution to the emissions of air pollutants. Among the various manufacturing processes, sintering is the major emitting process, which shares over half of the emissions of sulfur dioxide (SO2 ), nitrogen oxide (NOx ) and particulate matter (PM) for the entire industry. In this study we made a comprehensive evaluation of the air pollutant emissions from the sintering process of China's ISI in 2017 based on the Continuous Emission Monitoring System (CEMS) database and estimated the future reduction potentials. We found that there was a general decreasing trend of emission concentrations in the sintering flue gas in response to the strengthened emission control policies, but the mild increase of the oxygen content in the second half of the year flattened the decreasing trend, indicating the necessity for simultaneous control of the oxygen content in the flue gas. Despite the relative high standard-reaching rates of 90% to the emission concentration limits in GB 28662-2012, the standard-reaching rates to the ultra-low emission standards were only 12%, 40% and 27% for NOx, SO2 and PM respectively, with the lowest value mostly occurred in the western provinces. In 2017, the NOx, SO2 and PM emissions from the sintering process were 378.6 kt, 169.0 kt and 51.9 kt, respectively. If the ultra-low emission standards were met, the corresponding NOx, SO2 and PM emissions would decrease by 69.9%, 52.9%, and 56.4% respectively, illustrating large emission reducing potentials by achieving the ultra-low emission standards. Graphical abstract: Image 1 Highlights: Oxygen content was an important parameter for the evaluation of emission. Hebei province represented the largest contributor to the total emissions. There was still big gap to reach the ULE standard of NOx, SO2 and PM. The central and western regions should strengthen the control policies and measures.